Redescription of the Oriental genus Longicaudata Dmitriev (Hemiptera, Cicadomorpha: Cicadellidae) - Zhang, Hui; Zhang, Xiaoxia; Tian, Mingqian; Zhang, Bin (Zootaxa, 2026)
The Oriental genus Longicaudata Zhang & Wu is redescribed and redefined, along with detailed descriptions of L. trilineata Zhang & Wu is also provided. This study presents the first photographic documentation of L. trilineata and includes a key for species identification.